Silicon monoxide composite negative electrode material and preparation method and application thereof

By classifying the particle size of the silica powder, compounding it with the porous framework material and then coating it with carbon, the problem of stability and low first Coulombic efficiency caused by the volume expansion of the silica material during the cycle is solved. , achieving efficient and stable battery performance and effective utilization of resources.

CN119340357AActive Publication Date: 2025-01-21ZHEJIANG LICHEN NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411260201.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-21
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The silicon oxide material cracks and powders due to volume expansion during circulation, affecting the circulation stability; at the same time, irreversible inert substances are formed during the first implantation of lithium, resulting in low efficiency for the first time; in addition, fine powder cannot be produced during the airflow crushing process Effective utilization leads to waste of resources and increased production costs.

Method used

By classifying the silica powder according to particle size, and using amide solvents and ketone solvents to treat the silica powder and porous framework materials respectively, forming a composite and then carbon coating, a high-efficiency and Silicone oxide composite anode material with long cycle stability.

Benefits of technology

The first Coulombic efficiency and cycle stability of the silicon oxide composite anode material are improved, the preparation cost is reduced, and the fine powder produced during the airflow pulverization process is effectively utilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005035896020000221
    Figure BDA0005035896020000221
Patent Text Reader

Abstract

The invention relates to a silicon monoxide composite negative electrode material and a preparation method and application thereof, and the preparation method of the silicon monoxide composite negative electrode material comprises the following steps: carrying out grading treatment on silicon monoxide powder according to particle sizes to obtain silicon monoxide powder of multiple grades; treating each grade of silicon monoxide powder by utilizing an amide solvent to obtain silicon monoxide powder of which the surface is coated with the amide solvent; treating the porous framework material by utilizing a ketone solvent to obtain a porous framework material with a pore channel containing the ketone solvent; sequentially compounding the silicon monoxide powder coated with the amide solvent on the surface with a porous framework material containing a ketone solvent in a pore channel according to grades to obtain a complex; and carrying out carbon coating on the composite body to obtain the silicon monoxide composite negative electrode material. The silicon monoxide composite negative electrode material prepared by the preparation method not only has the characteristics of high first efficiency and long cycle stability, but also is low in preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a silicon oxide composite negative electrode material and a preparation method and application thereof. Background Art

[0002] Silicon oxide materials have a high theoretical specific capacity (>2000mAh / g), a low lithium storage reaction voltage platform, and low preparation cost, making them a very promising negative electrode material to replace graphite. However, during the repeated ion insertion and extraction process, silicon oxide materials will still experience cracking and powdering due to the large volume expansion, which greatly affects the cycle stability of silicon oxide materials. At the same time, silicon oxide materials will form Li when they are first inserted into lithium. 2 O and Li 4 SiO 4 Irreversible inert substances such as quartz and niobium cause its first coulombic efficiency to be low; in addition, in the preparation of silicon monoxide negative electrode materials, a large amount of fine powder is produced during the air flow crushing process, which cannot be effectively utilized, resulting in a huge waste of resources and an increase in preparation costs.

[0003] Therefore, there is an urgent need to provide a method for preparing silicon monoxide composite negative electrode materials with high initial efficiency and long cycle stability in a low-cost manner. Summary of the invention

[0004] Based on this, it is necessary to provide a silicon oxide composite negative electrode material and its preparation method and application to address the above problems. The silicon oxide composite negative electrode material prepared by the preparation method not only has the characteristics of high initial efficiency and long cycle stability, but also has low preparation cost.

[0005] A method for preparing a silicon oxide composite negative electrode material comprises the following steps:

[0006] The silicon oxide powder is graded according to the particle size to obtain silicon oxide powder of multiple grades;

[0007] Using an amide solvent to treat each level of silicon oxide powder respectively, to obtain silicon oxide powder with the amide solvent coated on the surface;

[0008] Treating the porous skeleton material with a ketone solvent to obtain a porous skeleton material containing the ketone solvent in the pores;

[0009] The silicon oxide powder coated with an amide solvent on the surface is compounded with a porous skeleton material containing a ketone solvent in the pores in order of grade to obtain a composite;

[0010] The composite is carbon coated to obtain a silicon oxide composite negative electrode material.

[0011] In one embodiment, in the step of subjecting silicon dioxide powder to classification to obtain silicon dioxide powder of multiple levels, at least one of the following conditions is satisfied:

[0012] (1) The median particle size of the silicon oxide powder is 20nm-500nm;

[0013] (2) Among the multiple levels of silicon oxide powder, the median particle size ratio of adjacent levels of silicon oxide powder is 1:1.5-1:3;

[0014] (3) The silicon iodine powder is silicon iodine fine powder produced during air flow milling.

[0015] In one embodiment, when the multiple levels of silicon oxide powder include first-level silicon oxide powder, second-level silicon oxide powder and third-level silicon oxide powder, at least one of the following conditions is met:

[0016] (1) The median particle size of the first-stage silicon oxide powder is 20nm-50nm;

[0017] (2) The median particle size of the second-stage silicon oxide powder is 50nm-100nm;

[0018] (3) The median particle size of the third-grade silicon oxide powder is 100nm-500nm;

[0019] (4) The mass ratio of the porous skeleton material to the first-stage silicon oxide powder is 1:0.5-1:0.7;

[0020] (5) The mass ratio of the porous skeleton material to the second-stage silicon oxide powder is 1:0.1-1:0.2;

[0021] (6) The mass ratio of the porous skeleton material to the third-level silicon oxide powder is 1:0.05-1:0.1.

[0022] In one embodiment, silicon dioxide powder coated with an amide solvent on the surface is compounded with the treated porous skeleton material in order from small to large.

[0023] In one embodiment, in the step of treating the porous skeleton material with a ketone solvent, at least one of the following conditions is met:

[0024] (1) The pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward;

[0025] (2) The average pore size of the porous framework material is 10 nm to 500 nm;

[0026] (3) The specific surface area of ​​the porous skeleton material is 190 m 2 / g-210m 2 / g;

[0027] (4) The porosity of the porous skeleton material is 50%-60%;

[0028] (5) The porous skeleton material is selected from porous carbon-nitrogen materials.

[0029] In one embodiment, when the pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward, silicon dioxide powder coated with an amide solvent on the surface is compounded with the treated porous skeleton material in order from small to large.

[0030] A silicon oxide composite negative electrode material, comprising an inner core and a carbon coating layer coated on the surface of the inner core, wherein the inner core comprises a porous skeleton material, the pores of the porous skeleton material are filled with a plurality of silicon oxide particle layers, and the particle size levels of the silicon oxide particles in each silicon oxide particle layer are different.

[0031] In one embodiment, the silicon 2 Oxide composite negative electrode material satisfies at least one of the following conditions:

[0032] (1) The filling amount of the silicon oxide particles is 65%-90% of the total mass of the core;

[0033] (2) The pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward;

[0034] (3) multiple silicon oxide particle layers are sequentially filled into the pores of the porous framework material in order of particle size from small to large;

[0035] (4) The thickness of the carbon coating layer is 3nm-5nm.

[0036] A negative electrode sheet prepared using the silicon monoxide composite negative electrode material as described above.

[0037] A secondary battery prepared using the negative electrode sheet as described above.

[0038] In the preparation method of the silicon dioxide composite negative electrode material of the present invention, silicon dioxide powder with an amide solvent coated on the surface and a porous skeleton material containing a ketone solvent in the pores are provided, and hydrogen bonds are formed between the ketone solvent and the amide solvent, and the binding force is strong, so that the silicon dioxide powder can be accurately anchored in the pores of the porous skeleton material, so that the silicon dioxide can fully utilize the buffer space provided by the pores of the porous skeleton material, reduce the expansion coefficient and agglomeration risk of silicon dioxide, and improve the first coulomb efficiency of the silicon dioxide composite negative electrode material; moreover, since the silicon dioxide powder is compounded with the porous skeleton material in sequence according to the level, the filling amount of the silicon dioxide powder can be increased, and then the purpose of fully recycling the silicon dioxide powder is achieved, and the preparation cost is reduced; at the same time, through carbon coating, the structural stability and conductivity of the porous skeleton material can be improved, and the contact between the electrolyte and the silicon dioxide powder can also be reduced, thereby improving the cycle stability of the silicon dioxide composite negative electrode material.

[0039] In addition, in the present invention, the silicon oxide powder can be silicon oxide fine powder produced in the process of air flow pulverization, thereby achieving the purpose of saving resources and reducing preparation costs.

[0040] Therefore, the silicon 2 Oxide composite negative electrode material prepared by the method for preparing the silicon 2 Oxide composite negative electrode material of the present invention not only has the characteristics of high initial efficiency and long cycle stability, but also has low preparation cost. DETAILED DESCRIPTION

[0041] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0043] The method for preparing the silicon monoxide composite negative electrode material provided by the present invention comprises the following steps:

[0044] S1, classifying silicon oxide powder according to particle size to obtain silicon oxide powder of multiple levels;

[0045] S2, treating each level of silicon dioxide powder with an amide solvent to obtain silicon dioxide powder with the amide solvent coated on the surface;

[0046] S3, treating the porous skeleton material with a ketone solvent to obtain a porous skeleton material containing the ketone solvent in the pores;

[0047] S4, compounding the silicon dioxide powder coated with an amide solvent on the surface with the porous skeleton material containing a ketone solvent in the pores in order according to the grade, to obtain a composite;

[0048] S5, carbon-coating the composite to obtain a silicon 2 oxide composite negative electrode material.

[0049] In the preparation method of the silicon iodine composite negative electrode material of the present invention, each level of silicon iodine powder is treated with an amide solvent respectively, so that the surface of each level of silicon iodine powder is coated with an amide solvent, that is, silicon iodine powder with the surface coated with an amide solvent is obtained, and at the same time, the porous skeleton material is treated with a ketone solvent to obtain a porous skeleton material with the ketone solvent adsorbed in the pores.

[0050] Since hydrogen bonds are formed between ketone solvents and amide solvents, and the bonding force is strong, when the silica powder coated with amide solvents on the surface is composited with the porous skeleton material containing ketone solvents in the pores, the silica powder can be accurately anchored in the pores of the porous skeleton material, avoiding the silica powder from being composited on the surface of the porous skeleton material, so that the silica can make full use of the buffer space provided by the pores of the porous skeleton material, reduce the expansion coefficient and agglomeration risk of silica, and improve the first coulombic efficiency of the silica composite negative electrode material; moreover, since the silica powder coated with amide solvents on the surface is composited with the porous skeleton material containing ketone solvents in the pores in sequence according to the level, it is convenient to better fill the silica powder of different particle sizes into the pores of the porous skeleton material, so that the silica powder of different particle sizes can be fully combined with the porous skeleton material, thereby increasing the filling amount of the silica powder, and then achieving the purpose of fully recycling the silica powder and reducing the preparation cost.

[0051] At the same time, by carbon coating the composite, the structural stability and conductivity of the porous skeleton material can be improved, and the contact between the electrolyte and the silicon oxide powder can be reduced, thereby improving the cycle stability of the silicon oxide composite negative electrode material.

[0052] Therefore, the silicon 2 Oxide composite negative electrode material prepared by the method for preparing the silicon 2 Oxide composite negative electrode material of the present invention not only has the characteristics of high initial efficiency and long cycle stability, but also has low preparation cost.

[0053] In step S1, the silicon oxide powder is silicon oxide fine powder produced in the process of air flow pulverization, or silicon oxide fine powder obtained by further pulverizing silicon oxide micropowder through air flow, thereby achieving the purpose of saving resources and reducing preparation costs.

[0054] Wherein, the median particle size of the silicon oxide powder is 20nm-500nm. It can be understood that the median particle size of the silicon oxide powder includes but is not limited to 20nm, 80nm, 100nm, 120nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 400nm, 450nm, and 500nm.

[0055] Optionally, among multiple levels of silicon nitride powder, the median particle size ratio of adjacent levels of silicon nitride powder is 1:1.5-1:3, preferably 1:2-1:2.5. It can be understood that the median particle size of the silicon nitride powder includes but is not limited to 1:1.5, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.5, and 1:3.

[0056] In the present invention, the multiple levels of silica powder can be two levels of silica powder, or three levels of silica powder, or four levels of silica powder, etc. Considering the difficulty of grading silica powder and the filling condition of silica powder in the porous skeleton material, three levels of silica powder are preferred in the present invention.

[0057] Further, when the multiple levels of silicon oxide powder are three levels of silicon oxide powder, the three levels of silicon oxide powder include first-level silicon oxide powder, second-level silicon oxide powder and third-level silicon oxide powder.

[0058] The median particle size of the first-stage silicon oxide powder is 20nm-50nm; it can be understood that the median particle size of the first-stage silicon oxide powder includes but is not limited to 20nm, 30nm, 40nm, and 50nm.

[0059] The median particle size of the second-level silicon oxide powder is 50nm-100nm; it can be understood that the median particle size of the second-level silicon oxide powder includes but is not limited to 50nm, 60nm, 70nm, 80nm, 90nm, and 100nm.

[0060] The median particle size of the third-grade silicon oxide powder is 100nm-500nm. It can be understood that the median particle size of the third-grade silicon oxide powder includes but is not limited to 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, and 500nm.

[0061] In the present invention, by controlling the median particle size of silicon oxide powders of different levels, the filling amount of silicon oxide powders of different particle sizes in the pores of the porous skeleton material is increased, and the structural stability of the silicon oxide composite negative electrode material is further improved.

[0062] It should be noted that in step S1, among the multiple levels of silicon monoxide powder, a higher level means a higher median particle size of the silicon monoxide powder.

[0063] In step S2, the specific steps of using amide solvents to treat each level of silicon dioxide powder are as follows: each level of silicon dioxide powder is placed in an amide solvent for treatment, and excess amide solvent is removed by filtering, so that the surface of each level of silicon dioxide powder is coated with amide solvent.

[0064] In one embodiment, the amide solvent is selected from at least one of N,N-dimethylformamide (DMF), acetamide, and benzamide, preferably N,N-dimethylformamide.

[0065] In step S3, the porous skeleton material is placed in a ketone solvent for treatment, and the ketone solvent adsorbed on the surface of the porous skeleton material is removed by washing to obtain a porous skeleton material containing the ketone solvent in the pores.

[0066] Optionally, the pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward, so that the pore structure is wide on the outside and narrow on the inside, which is conducive to the filling of silicon oxide powder in the pores of the porous skeleton material, and can ensure the dispersion of silicon oxide powder in the pores to a certain extent, and better prevent the agglomeration of silicon oxide powder.

[0067] Furthermore, considering the filling amount of silicon dioxide powder in the porous skeleton material, when the pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward, in step S4, the silicon dioxide powder coated with amide solvent on the surface is compounded with the treated porous skeleton material in order from small to large. Such an arrangement can further increase the filling amount of silicon dioxide powder in the porous skeleton material, and can better recycle silicon dioxide powder.

[0068] Optionally, the average pore size of the porous skeleton material is 10nm-500nm; it can be understood that the average pore size of the porous skeleton material includes but is not limited to 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm.

[0069] Optionally, the specific surface area of ​​the porous skeleton material is 190 m 2 / g-210m 2 / g; It can be understood that the specific surface area of ​​the porous skeleton material is not limited to 190m 2 / g, 195m 2 / g, 200m 2 / g, 205m 2 / g, 210m 2 / g.

[0070] Optionally, the porosity of the porous skeleton material is 50%-60%; it can be understood that the porosity of the porous skeleton material includes but is not limited to 50%, 55%, and 60%.

[0071] In the present invention, by controlling the average pore size, specific surface area and porosity of the porous skeleton material, the filling amount of silicon oxide powder in the porous skeleton material can be further increased, the recycling of silicon oxide powder can be better realized, the preparation cost can be reduced, and at the same time, the structural stability of the porous skeleton material can be better guaranteed, thereby effectively improving the initial efficiency and cycle stability of the silicon oxide composite negative electrode material.

[0072] In the present invention, the porous skeleton material is selected from any one of porous carbon-nitrogen material, porous ceramic or porous carbon material, preferably porous carbon-nitrogen material. In this way, the incorporation of nitrogen can bring high electron mobility and higher capacity retention and rate performance to the porous skeleton material.

[0073] The porous carbon nitride material in the present invention can be purchased from the market, or can be prepared by referring to the following method for preparing the porous carbon nitride material.

[0074] Specifically, the preparation method of the porous carbon nitride material comprises the following steps:

[0075] S31, mixing a carbon-nitrogen-containing compound, a pore-forming agent and deionized water to obtain a mixed solution, and then subjecting the mixed solution to a rotary evaporation drying treatment to obtain an intermediate;

[0076] S32, sintering the intermediate at high temperature under a protective gas atmosphere to obtain a porous carbon-nitrogen material.

[0077] In step S31, the mass ratio of the carbon-nitrogen-containing compound to the pore-forming agent is 25:1-40:1, preferably 30:1.

[0078] Furthermore, the carbon-nitrogen-containing compound is selected from at least one of dicyandiamide, urea or melamine; the pore-forming agent is selected from ammonium bicarbonate, potassium hydroxide or sodium chloride. Since ammonium bicarbonate has a low thermal decomposition temperature, ammonium bicarbonate is preferably used in the present invention.

[0079] In step S32, the high temperature sintering temperature is 450°C-650°C, preferably 500°C, and the high temperature sintering time is 5h-8h, preferably 6h.

[0080] In one embodiment, the protective gas atmosphere may be an argon atmosphere.

[0081] It should be noted that the pore structure of the porous carbon-nitrogen material prepared by the above method in the present invention gradually decreases from the outer surface of the porous skeleton material inward, that is, it is wide outside and narrow inside. The reason is that the carbon dioxide and ammonia gases decomposed by the pore-forming agent (such as ammonium bicarbonate) are released from the inside to the outside. The outward pressure becomes smaller, resulting in the outward pore size becoming larger and larger, thus forming a wide outside and narrow inside.

[0082] In one embodiment, the porous carbon nitride material is in the shape of a sheet, and the pores are not multi-level pores that are interconnected. This arrangement is helpful in avoiding the agglomeration of silicon dioxide powder.

[0083] In one embodiment, multiple centrifugal washings are used to remove ketone solvents on the surface of the porous skeleton material, so that the outer surface of the porous skeleton material containing ketone solvents in the pores contains almost no ketone solvents, thereby better ensuring that the silicon dioxide powder is accurately embedded in the pores of the porous skeleton material.

[0084] In one embodiment, the ketone solvent is selected from at least one of acetone, methyl ethyl ketone, and cyclohexanone, preferably acetone.

[0085] In step S4, when the silicon oxide powder coated with the amide solvent on the surface is compounded with the porous skeleton material containing the ketone solvent in the pores in sequence according to the stepwise addition method, the order of the order is not particularly limited.

[0086] For example, when multiple levels of silica powder include first-level silica powder, second-level silica powder and third-level silica powder, they can be compounded in order from small to large, that is, the first-level silica powder with amide solvent coated on the surface, the second-level silica powder with amide solvent coated on the surface, and the third-level silica powder with amide solvent coated on the surface can be compounded with the porous skeleton material containing ketone solvent in the pores; they can also be compounded in order from large to small, that is, the third-level silica powder with amide solvent coated on the surface, the second-level silica powder with amide solvent coated on the surface, and the first-level silica powder with amide solvent coated on the surface can be compounded with the porous skeleton material containing ketone solvent in the pores.

[0087] Of course, it can also be carried out in the following manner, for example, the first-level silicon oxide powder with an amide solvent coated on the surface, the third-level silicon oxide powder with an amide solvent coated on the surface, and the second-level silicon oxide powder with an amide solvent coated on the surface are sequentially compounded with a porous skeleton material containing a ketone solvent in the pores, or the third-level silicon oxide powder with an amide solvent coated on the surface, the first-level silicon oxide powder with an amide solvent coated on the surface, and the second-level silicon oxide powder with an amide solvent coated on the surface are sequentially compounded with a porous skeleton material containing a ketone solvent in the pores, or the second-level silicon oxide powder with an amide solvent coated on the surface, the first-level silicon oxide powder with an amide solvent coated on the surface, and the third-level silicon oxide powder with an amide solvent coated on the surface are sequentially compounded with a porous skeleton material containing a ketone solvent in the pores, etc.

[0088] Considering the filling amount of silicon dioxide powder in the porous skeleton material, in the present invention, it is preferred to compound the silicon dioxide powder coated with an amide solvent on the surface with the treated porous skeleton material in order from small to large levels.

[0089] In one embodiment, the specific steps of compounding silicon dioxide powder coated with amide solvents on the surface with porous skeleton materials containing ketone solvents in the pores in order of grade are as follows: silicon dioxide powder coated with amide solvents on the surface are mixed with porous skeleton materials containing ketone solvents in the pores and solvent in order of grade to obtain a mixed solution, and then the mixed solution is washed and dried.

[0090] Specifically, when the multiple levels of silica powder are three levels of silica powder, namely, first-level silica powder, second-level silica powder and third-level silica powder, the first-level silica powder coated with an amide solvent on the surface is mixed with a porous skeleton material containing a ketone solvent in the pores and a solvent to obtain a first mixed solution; then, the second-level silica powder coated with an amide solvent on the surface is added to the first mixed solution to obtain a second mixed solution; then, the third-level silica powder coated with an amide solvent on the surface is added to the third mixed solution to obtain a third mixed solution; finally, the third mixed solution is washed and dried to obtain a composite.

[0091] It is understandable that in step S3, some ketone solvents will inevitably remain on the surface of the porous skeleton material containing ketone solvents in the pores obtained, resulting in some silica powder being adsorbed on the surface of the porous skeleton material when the porous skeleton material containing ketone solvents in the pores is mixed with silica powder coated with amide solvents on the surface. These silica powders will be completely removed after washing. Therefore, in step S4, the silica powder in the prepared composite only exists in the pores of the porous skeleton material.

[0092] In one embodiment, multiple centrifugal washings are performed to remove silicon oxide powder with weak bonding force on the surface of the porous skeleton material.

[0093] In one embodiment, the solvent may be water.

[0094] In one embodiment, the drying temperature is 70°C-90°C, preferably 80°C.

[0095] Optionally, the mass ratio of the porous skeleton material to the first-stage silicon dioxide powder is 1:0.3-1:0.8, preferably 1:0.5-1:0.7.

[0096] Optionally, the mass ratio of the porous skeleton material to the second-stage silicon dioxide powder is 1:0.05-1:0.3, preferably 1:0.1-1:0.2.

[0097] Optionally, the mass ratio of the porous skeleton material to the second-stage silicon dioxide powder is 1:0.01-1:0.15, preferably 1:0.05-1:0.1.

[0098] In the present invention, by controlling the amount of silica powder added to the porous skeleton material and each level, the silica powder can be better embedded in the pores of the porous skeleton material, thereby better recycling the silica powder and increasing the filling amount of silica powder in the porous skeleton material.

[0099] In step S5, the carbon coating method is selected from any one of gas phase coating, liquid phase coating or solid phase coating, preferably gas phase coating, which is conducive to obtaining a uniform carbon coating layer.

[0100] Specifically, in the gas phase coating method, the gas source is selected from at least one of acetylene, methane, ethane, propane, and ethylene; the gas source flow rate is 5L / min-20L / min; the carbon coating temperature is 800℃-1000℃, and the carbon coating time is 120min-300min.

[0101] Furthermore, after the carbon coating is completed, carbonization treatment is performed to obtain a silicon oxide composite negative electrode material, wherein the carbonization temperature is 800° C.-1000° C. and the carbonization time is 60 min-180 min.

[0102] In the present invention, by controlling various process parameters in the gas phase coating method, a uniform carbon coating layer can be obtained, which is conducive to building a more complete conductive network and improving the conductivity and structural stability of the silicon monoxide composite negative electrode material.

[0103] At the same time, the present invention also provides a silicon oxide composite negative electrode material, the silicon oxide composite negative electrode material comprises a core and a carbon coating layer coated on the surface of the core, the core comprises a porous skeleton material, the pores of the porous skeleton material are filled with a plurality of silicon oxide particle layers, and the particle size of the silicon oxide particles in each silicon oxide particle layer is different. The silicon oxide composite negative electrode material has the characteristics of high first efficiency and long cycle stability, and has low preparation cost.

[0104] Optionally, the filling amount of the silicon monoxide particles is 65%-90% of the total mass of the inner core, preferably 80%-90%.

[0105] Optionally, the pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward.

[0106] Optionally, a plurality of silicon oxide particle layers are sequentially filled into the pores of the porous skeleton material in order of particle size from small to large.

[0107] Optionally, the thickness of the carbon coating layer is 3nm-5nm. Such a configuration is conducive to forming a complete conductive network, and is also conducive to improving the structural stability of the silicon oxide composite negative electrode material, thereby improving the cycle stability of the silicon oxide composite negative electrode material.

[0108] In addition, the present invention also provides a negative electrode sheet prepared using the silicon monoxide composite negative electrode material as described above.

[0109] And, a secondary battery prepared using the negative electrode sheet as described above.

[0110] The following specific examples will further illustrate the silicon oxide composite negative electrode material and its preparation method and application. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0111] Example 1

[0112] Silica powder with a median particle size of 20nm-500nm is graded to obtain first-grade silica powder, second-grade silica powder and third-grade silica powder, wherein the first-grade silica powder has a median particle size of 20nm-50nm, the second-grade silica powder has a median particle size of 50nm-100nm, and the third-grade silica powder has a median particle size of 100nm-500nm.

[0113] 300g of the first-grade silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated first-grade silicon oxide powder; 50g of the second-grade silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated second-grade silicon oxide powder; 25g of the third-grade silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated third-grade silicon oxide powder.

[0114] 1000g of dicyandiamide, 35g of ammonium bicarbonate and 500mL of deionized water were mixed and stirred for 5h, and dried by rotary evaporation to obtain an intermediate, and then the intermediate was sintered at 500°C for 6h under argon conditions to obtain a porous carbon nitride material, wherein the porous carbon nitride material has a sheet shape, a pore structure of wide outside and narrow inside, an average pore diameter of 300nm, and a specific surface area of ​​205m 2 / g, the porosity is 55%; then 500g of the porous carbon nitride material is placed in an acetone solvent and stirred for 2h, and then centrifuged and washed three times with clean water to obtain the treated porous carbon nitride material.

[0115] The first-level silicon dioxide powder obtained above is mixed with the treated porous carbon nitride material obtained above and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution; then the treated second-level silicon dioxide powder obtained above is added to the first mixed solution, and stirred for 6 hours to obtain a second mixed solution; then the treated third-level silicon dioxide powder obtained above is added to the second mixed solution, and stirred for 8 hours to obtain a third mixed solution; the third mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite.

[0116] The above-obtained composite is carbon-coated by a gas phase coating method, wherein, in the gas phase coating method, the gas source is acetylene, the gas source flow rate is 10L / min, the carbon coating time is 180min, the carbon coating temperature is 900°C, and then the mixture is heated for 30min to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 85%, and the thickness of the carbon coating layer is 4nm.

[0117] Example 2

[0118] Silica powder with a median particle size of 20nm-500nm is graded to obtain first-grade silica powder, second-grade silica powder and third-grade silica powder, wherein the median particle size of the first-grade silica powder is 40nm-50nm, the median particle size of the second-grade silica powder is 80nm-100nm, and the median particle size of the third-grade silica powder is 200nm-300nm.

[0119] 350g of the first-grade silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated first-grade silicon oxide powder; 100g of the second-grade silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated second-grade silicon oxide powder; 50g of the third-grade silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated third-grade silicon oxide powder.

[0120] 1000g of dicyandiamide, 40g of ammonium bicarbonate and 500mL of deionized water were mixed and stirred for 5h, and dried by rotary evaporation to obtain an intermediate, and then the intermediate was sintered at 500°C for 6h under argon conditions to obtain a porous carbon nitride material, wherein the porous carbon nitride material has a sheet shape, a pore structure of wide outside and narrow inside, an average pore diameter of 450nm, and a specific surface area of ​​190m 2 / g, the porosity is 50%; then 500g of the porous carbon nitride material is placed in an acetone solvent and stirred for 2h, and then centrifuged and washed three times with clean water to obtain the treated porous carbon nitride material.

[0121] The first-level silicon dioxide powder obtained above is mixed with the treated porous carbon nitride material obtained above and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution; then the treated second-level silicon dioxide powder obtained above is added to the first mixed solution, and stirred for 6 hours to obtain a second mixed solution; then the treated third-level silicon dioxide powder obtained above is added to the second mixed solution, and stirred for 8 hours to obtain a third mixed solution; the third mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite.

[0122] The above-obtained composite is carbon-coated by a gas phase coating method, wherein, in the gas phase coating method, the gas source is acetylene, the gas source flow rate is 15L / min, the carbon coating time is 300min, the carbon coating temperature is 1000°C, and then the mixture is kept warm for 180min to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 90%, and the thickness of the carbon coating layer is 5nm.

[0123] Example 3

[0124] Silica powder with a median particle size of 20nm-500nm is graded to obtain first-grade silica powder, second-grade silica powder and third-grade silica powder, wherein the median particle size of the first-grade silica powder is 20nm-30nm, the median particle size of the second-grade silica powder is 60nm-90nm, and the median particle size of the third-grade silica powder is 180nm-270nm.

[0125] 200g of the first-level silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated first-level silicon oxide powder; 30g of the second-level silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated second-level silicon oxide powder; 15g of the third-level silicon oxide powder was placed in a DMF solution and stirred for 2h, then filtered to obtain the treated third-level silicon oxide powder.

[0126] 1000g of dicyandiamide, 25g of ammonium bicarbonate and 500mL of deionized water were mixed and stirred for 5h, and dried by rotary evaporation to obtain an intermediate, and then the intermediate was sintered at 500°C for 6h under argon conditions to obtain a porous carbon nitride material, wherein the porous carbon nitride material has a sheet shape, a pore structure of wide outside and narrow inside, an average pore diameter of 350nm, and a specific surface area of ​​210m 2 / g, the porosity is 60%; then 500g of the porous carbon nitride material is placed in an acetone solvent and stirred for 2h, and then centrifuged and washed three times with clean water to obtain the treated porous carbon nitride material.

[0127] The first-level silicon dioxide powder obtained above is mixed with the treated porous carbon nitride material obtained above and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution; then the treated second-level silicon dioxide powder obtained above is added to the first mixed solution, and stirred for 6 hours to obtain a second mixed solution; then the treated third-level silicon dioxide powder obtained above is added to the second mixed solution, and stirred for 8 hours to obtain a third mixed solution; the third mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite.

[0128] The above-obtained composite is carbon-coated by a gas phase coating method, wherein, in the gas phase coating method, the gas source is acetylene, the gas source flow rate is 5 L / min, the carbon coating time is 120 min, the carbon coating temperature is 800°C, and then the mixture is heated for 60 min to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 89%, and the thickness of the carbon coating layer is 3 nm.

[0129] Example 4

[0130] Compared with Example 1, Example 4 differs only in that the amount of the first-stage silicon oxide powder used is 200 g, and the other conditions are the same, thereby obtaining a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 82%, and the thickness of the carbon coating layer is 3.8 nm.

[0131] Example 5

[0132] Compared with Example 1, Example 5 differs only in that the amount of the first-stage silicon oxide powder used is 400 g, and the other conditions are the same, thereby obtaining a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 88%, and the thickness of the carbon coating layer is 3.6 nm.

[0133] Example 6

[0134] Compared with Example 1, Example 6 differs only in that the amount of the second-stage silicon oxide powder used is 150 g, and the other conditions are the same, thereby obtaining a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 87%, and the thickness of the carbon coating layer is 4.1 nm.

[0135] Example 7

[0136] Compared with Example 1, Example 7 differs only in that the amount of the third-level silicon oxide powder used is 50 g, and the other conditions are the same, thereby obtaining a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 81%, and the thickness of the carbon coating layer is 3.9 nm.

[0137] Example 8

[0138] Compared with Example 1, Example 8 differs only in that the median particle size of the first-level silicon oxide powder is 5nm-10nm, the median particle size of the second-level silicon oxide powder is 100nm-200nm, and the median particle size of the third-level silicon oxide powder is 400nm-500nm, and other conditions are the same, thereby obtaining a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 85%, and the thickness of the carbon coating layer is 3.9nm.

[0139] Example 9

[0140] Compared with Example 1, Example 9 differs only in that the third-level silicon oxide powder obtained above is mixed with the treated porous carbon-nitrogen material obtained above and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution; then the treated second-level silicon oxide powder obtained above is added to the first mixed solution, and stirred for 6 hours to obtain a second mixed solution; then the treated first-level silicon oxide powder obtained above is added to the second mixed solution, and stirred for 8 hours to obtain a third mixed solution; the third mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite, and the other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein, in the silicon oxide composite negative electrode material, the filling amount of silicon oxide particles is 65%, and the thickness of the carbon coating layer is 4.1 nm.

[0141] Example 10

[0142] Compared with Example 1, Example 10 differs only in that the first-level silicon oxide powder obtained above is mixed with the treated porous carbon-nitrogen material obtained above and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution; then the treated third-level silicon oxide powder obtained above is added to the first mixed solution, and stirred for 6 hours to obtain a second mixed solution; then the treated second-level silicon oxide powder obtained above is added to the second mixed solution, and stirred for 8 hours to obtain a third mixed solution; the third mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite, and the other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein, in the silicon oxide composite negative electrode material, the filling amount of silicon oxide particles is 75%, and the thickness of the carbon coating layer is 3.7 nm.

[0143] Embodiment 11

[0144] The difference between Example 11 and Example 1 is that commercial porous carbon (average pore size of about 50 nm, specific surface area of ​​1500 m 2 / g, porosity 60%) to replace the porous carbon nitrogen material, and other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 65%, and the thickness of the carbon coating layer is 4.2nm.

[0145] Example 12

[0146] The difference between Example 12 and Example 1 is that a porous carbon nanosheet is used to replace the porous carbon nitrogen material, wherein the porous carbon nanosheet is in the shape of a sheet, the pore structure is circular, the average pore diameter is about 100nm, and the specific surface area is 175m 2 / g, the porosity is 40%, and the other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 70%, and the thickness of the carbon coating layer is 5nm.

[0147] Example 13

[0148] Compared with Example 1, Example 13 differs only in that acetamide is used instead of DMF solution, and cyclohexanone is used instead of acetone solvent. Other conditions are the same, and a silicon oxide composite negative electrode material is obtained. In the silicon oxide composite negative electrode material, the filling amount of silicon oxide particles is 84%, and the thickness of the carbon coating layer is 4 nm.

[0149] Comparative Example 1

[0150] The only difference between Comparative Example 1 and Example 1 is that the step of grading the 20nm-500nm silicon dioxide powder is not included, that is, 375g of the 20nm-500nm silicon dioxide powder is directly placed in a DMF solution and stirred for 2h, and then filtered to obtain the treated silicon dioxide powder.

[0151] The treated silicon dioxide powder obtained above is evenly mixed with the treated porous carbon nitrogen material obtained above and 500 mL of water to obtain a mixed solution; the mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite, and the other conditions are the same to obtain a silicon dioxide composite negative electrode material, wherein the filling amount of silicon dioxide particles in the silicon dioxide composite negative electrode material is 50%, and the thickness of the carbon coating layer is 3.7 nm.

[0152] Comparative Example 2

[0153] Compared with Example 1, Comparative Example 2 differs only in that it does not contain the step of placing the first-level silicon oxide powder, the second-level silicon oxide powder and the third-level silicon oxide powder in DMF solution, stirring for 2 hours, and then filtering. That is, 300g of the first-level silicon oxide powder is directly mixed with the treated porous carbon-nitrogen material obtained above and 500mL of water, and stirred for 2 hours to obtain a first mixed solution; then 50g of the second-level silicon oxide powder is added to the first mixed solution, and stirred for 6 hours to obtain a second mixed solution; then 25g of the third-level silicon oxide powder is added to the second mixed solution, and stirred for 8 hours to obtain a third mixed solution; the third mixed solution obtained above is centrifuged and washed with water three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite, and the other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 63%, and the thickness of the carbon coating layer is 4.1nm.

[0154] Comparative Example 3

[0155] Compared with Example 1, Comparative Example 3 differs only in that it does not contain the step of placing 500 g of porous carbon-nitrogen material in an acetone solvent and stirring for 2 hours, and then centrifugally washing it with clean water three times to obtain the treated porous carbon-nitrogen material. That is, the first-level silicon oxide powder obtained above is directly mixed with 500 g of porous carbon-nitrogen material and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution. The other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 60%, and the thickness of the carbon coating layer is 3.9 nm.

[0156] Comparative Example 4

[0157] Compared with Example 1, Comparative Example 4 differs only in that the treated first-level silicon oxide powder, the treated second-level silicon oxide powder, the treated third-level silicon oxide powder, the treated porous carbon-nitrogen material and 500 mL of water are mixed and stirred for 2 hours to obtain a mixed solution; the mixed solution obtained above is centrifuged and washed three times, and then placed in a vacuum drying oven for drying at 80°C to obtain a composite, and the other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 52%, and the thickness of the carbon coating layer is 3.8 nm.

[0158] Comparative Example 5

[0159] The only difference between Comparative Example 5 and Example 1 is that 1000 g of dicyandiamide and 500 mL of deionized water are mixed and stirred for 5 h, and then dried by rotary evaporation to obtain an intermediate, and then the intermediate is sintered at 500 ° C for 6 h under argon conditions to obtain a carbon-nitrogen material; then 500 g of the carbon-nitrogen material is placed in an acetone solvent and stirred for 2 h, followed by centrifugal washing three times with clean water to obtain a treated carbon-nitrogen material.

[0160] The first-level silicon oxide powder obtained above is mixed with the treated carbon-nitrogen material obtained above and 500 mL of water, and stirred for 2 hours to obtain a first mixed solution. The other conditions are the same to obtain a silicon oxide composite negative electrode material, wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 5%, and the thickness of the carbon coating layer is 4.0 nm.

[0161] Comparative Example 6

[0162] Compared with Example 1, Comparative Example 6 differs only in that it does not contain the step of carbon-coating the above-obtained composite by the gas phase coating method, and the other conditions are the same, thereby obtaining a silicon oxide composite negative electrode material (i.e., a composite), wherein the filling amount of silicon oxide particles in the silicon oxide composite negative electrode material is 86%, and the thickness of the carbon coating layer is 10 nm.

[0163] Performance Test:

[0164] The electrochemical cycle performance of the silicon 2 Oxide composite negative electrode materials prepared in Examples 1-13 and Comparative Examples 1-6 was tested by the following method. The test results are shown in Table 1.

[0165] Among them, the silicon oxide composite negative electrode materials prepared in Examples 1-13 and Comparative Examples 1-6 were used as negative electrode materials to prepare button batteries, and the specific steps were as follows: the silicon oxide composite negative electrode material, conductive agent SP, dispersant CMC, and binder AONE obtained above were mixed in a mass ratio of 70:15:5:10, and water was used as a solvent to prepare a negative electrode slurry; the negative electrode slurry was coated on a copper foil, and a lithium sheet was used as a counter electrode and a Celgard 2400 microporous polypropylene film was used as a separator to prepare a button battery.

[0166] The button cell obtained above was tested on the Blue Electric Battery Test System CT2001A equipment. At 25°C, the charge and discharge cycle characteristics of the button cell were detected using the Blue Electric test cabinet, as follows: first, discharge to 0.005V at 0.1C, then discharge to 0.001V at 0.08C, discharge to 0.001V at 0.05C, discharge to 0.001V at 0.02C, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, and calculate the capacity retention rate after 100 cycles.

[0167] Table 1

[0168]

[0169] From the data of Example 1 and Examples 4-5 in Table 1, it can be seen that changing the input amount of the first-stage silicon oxide powder, for example, reducing the input amount can increase the cycle but the capacity decreases significantly. When the usage amount of the first-stage silicon oxide powder is increased, the silicon oxide powder will be suspended on the surface of the porous carbon nitride material, affecting the cycle retention rate.

[0170] From the data of Example 1 and Examples 6-7 in Table 1, it can be seen that the increase in the input amount of the second-level silicon oxide powder and the third-level silicon oxide powder will lead to excessive loading of the porous carbon nitrogen material, causing the battery to expand significantly in volume during the cycle process, resulting in a sharp decrease in the cycle stability of the battery.

[0171] From the data of Example 1 and Example 8 in Table 1, it can be seen that selecting appropriate median particle size of the first-level silicon oxide powder, the median particle size of the second-level silicon oxide powder, and the median particle size of the third-level silicon oxide powder is beneficial to increasing the filling amount of silicon oxide powder in the porous carbon-nitrogen material, thereby improving the cycle performance and first efficiency of the battery.

[0172] It can be seen from the data of Example 1 and Example 9 in Table 1 that since Example 9 did not compound the treated first-level silicon oxide powder, the treated second-level silicon oxide powder and the treated third-level silicon oxide powder with the treated porous skeleton material in sequence according to the particle size from small to large, the amount of silicon oxide powder embedded in the pores of the porous skeleton material is small, which is not good for the cycle and resistance of the battery.

[0173] From the data of Example 1 and Example 11 in Table 1, it can be seen that the use of a porous carbon-nitrogen material with a pore structure that is wide on the outside and narrow on the inside is beneficial to increasing the amount of silicon dioxide powder embedded in the pores of the porous skeleton material, while improving the cycle stability of the battery.

[0174] From the data of Example 1 and Examples 12-13 in Table 1, it can be seen that compounding the silicon dioxide powder coated with an amide solvent on the surface with the treated porous skeleton material in order from small to large levels is beneficial to increasing the amount of silicon dioxide powder embedded in the pores of the porous skeleton material and improving the cycle stability of the battery.

[0175] In addition, compared with Example 1, since the silicon oxide powder is not graded in Comparative Example 1, the amount of silicon oxide embedded in the pores is reduced, and most of it is directly compounded on the surface of the porous carbon nitride material, which is not good for the cycle and resistance of the battery.

[0176] Compared with Example 1, since the first-level silicon oxide powder, the second-level silicon oxide powder and the third-level silicon oxide powder were not treated with DMF solution in Comparative Example 2, and the porous carbon nitride material was not treated with acetone solution in Comparative Example 3, silicon oxide could not be accurately embedded in the pores of the porous carbon nitride material, resulting in a reduction in the amount of silicon oxide in the pores, and most of it was directly compounded on the surface of the porous carbon nitride material, which is not good for the cycle and resistance of the battery.

[0177] Compared with Example 1, in Comparative Example 4, since the first-level silicon oxide powder, the second-level silicon oxide powder and the third-level silicon oxide powder are directly mixed with the porous carbon nitride material, the amount of silicon oxide embedded in the pores is reduced, and most of it is directly compounded on the surface of the porous carbon nitride material, which is not good for the cycle and resistance of the battery.

[0178] Compared with Example 1, in Comparative Example 5, since a non-porous carbon nitride material is used as a carrier to composite with silicon oxide, part of the silicon oxide is wrapped and part is exposed. In the later gas phase coating process, silicon oxide will agglomerate, resulting in a significant decrease in battery efficiency in the later stage of the cycle.

[0179] Compared with Example 1, since no carbon layer coating is performed in Comparative Example 6, silicon monoxide is directly exposed to the electrolyte, and the volume expands during the cycle, the cycle rate decreases, and the conductivity is poor.

[0180] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0181] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a silicon oxide composite negative electrode material, characterized in that: The following steps are involved: The silicon oxide powder is graded according to the particle size to obtain silicon oxide powder of multiple grades; Using an amide solvent to treat each level of silicon oxide powder respectively, to obtain silicon oxide powder with the amide solvent coated on the surface; Treating the porous skeleton material with a ketone solvent to obtain a porous skeleton material containing the ketone solvent in the pores; The silicon oxide powder coated with an amide solvent on the surface is compounded with a porous skeleton material containing a ketone solvent in the pores in order of grade to obtain a composite; The composite is carbon coated to obtain a silicon oxide composite negative electrode material.

2. The method for preparing the silicon 2 Oxide composite negative electrode material according to claim 1, characterized in that: In the step of subjecting the silicon oxide powder to classification to obtain silicon oxide powder of multiple grades, at least one of the following conditions is met: (1) The median particle size of the silicon oxide powder is 20nm-500nm; (2) Among the multiple levels of silicon oxide powder, the median particle size ratio of adjacent levels of silicon oxide powder is 1:1.5-1:3; (3) The silicon iodine powder is silicon iodine fine powder produced during air flow milling.

3. The method for preparing the silicon 2 Oxide composite negative electrode material according to claim 2, characterized in that: When the multiple levels of silicon oxide powder include first-level silicon oxide powder, second-level silicon oxide powder and third-level silicon oxide powder, at least one of the following conditions is met: (1) The median particle size of the first-stage silicon oxide powder is 20nm-50nm; (2) The median particle size of the second-stage silicon oxide powder is 50nm-100nm; (3) The median particle size of the third-grade silicon oxide powder is 100nm-500nm; (4) The mass ratio of the porous skeleton material to the first-stage silicon oxide powder is 1:0.5-1:0.7; (5) The mass ratio of the porous skeleton material to the second-stage silicon oxide powder is 1:0.1-1:0.2; (6) The mass ratio of the porous skeleton material to the third-level silicon oxide powder is 1:0.05-1:0.

1.

4. The method for preparing the silicon 2 Oxide composite negative electrode material according to claim 1, characterized in that: The silicon dioxide powders coated with amide solvents on the surface are compounded with the treated porous skeleton material in order from small to large.

5. The method for preparing the silicon 2 Oxide composite negative electrode material according to claim 1, characterized in that: In the step of treating the porous skeleton material with a ketone solvent, at least one of the following conditions is met: (1) The pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward; (2) The average pore size of the porous framework material is 10 nm to 500 nm; (3) The specific surface area of ​​the porous skeleton material is 190 m 2 / g-210m 2 / g; (4) The porosity of the porous skeleton material is 50%-60%; (5) The porous skeleton material is selected from porous carbon-nitrogen materials.

6. The method for preparing the silicon 2 Oxide composite negative electrode material according to claim 4, characterized in that: When the pore structure of the porous skeleton material gradually decreases inward from the outer surface of the porous skeleton material, silicon dioxide powder coated with amide solvent on the surface is compounded with the treated porous skeleton material in order from small to large levels.

7. A silicon oxide composite negative electrode material, characterized in that: The silicon iodine composite negative electrode material comprises a core and a carbon coating layer coated on the surface of the core, wherein the core comprises a porous skeleton material, the pores of the porous skeleton material are filled with a plurality of silicon iodine particle layers, and the particle size levels of the silicon iodine particles in each silicon iodine particle layer are different.

8. The silicon 2 Oxide composite negative electrode material according to claim 7, characterized in that: The silicon dioxide composite negative electrode material meets at least one of the following conditions: (1) The filling amount of the silicon oxide particles is 65%-90% of the total mass of the core; (2) The pore structure of the porous skeleton material gradually decreases from the outer surface of the porous skeleton material inward; (3) multiple silicon oxide particle layers are sequentially filled into the pores of the porous framework material in order of particle size from small to large; (4) The thickness of the carbon coating layer is 3nm-5nm.

9. A negative electrode sheet prepared using the silicon 2 Oxide composite negative electrode material as claimed in claim 7 or 8.

10. A secondary battery prepared using the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Silicon monoxide-based composite negative electrode material capable of improving first coulombic efficiency and preparation method of silicon monoxide-based composite negative electrode material

    CN113224279A

  • High-performance silicon-oxygen negative electrode material as well as preparation method and application thereof

    CN115020688A

  • Low-expansion silicon-based composite material as well as preparation method and application thereof

    CN115117327A

  • Silicon monoxide-based negative electrode composite material with core-shell structure and preparation method of silicon monoxide-based negative electrode composite material

    CN116741951A

  • Anode material, preparation method thereof, and lithium ion battery

    US20250051166A1